The Anatomical Distribution of Colorectal Carcinoma A Ten - Year Study (1990- 2000) - SA Jalali; SM Jalali (Tehran University of Medical Sciences, 2002)
Colorectal carcinoma is the most common gastrointestinal malignancy in the United States of America. In women the incidence is second to breast carcinoma; and in men it is the third most common carcinoma after lung and prostatic carcinoma. The overal incidence of colorectal carcinoma has had an increase in the first half of the past century, and has remained unchanged since. But the anatomic location has changed in the past 30 years, so that in the west 75% of the involvement was in the last 25 centimeters of the large bowel and within the reach of rigid sigmoidoscopy in those earlier years. But recent data shows that this figure is close to 60%, and since the total incidence has not changed, the right sided involvement has increased. In Iran there has been a change quite dissimilar with changes in the United States. In a study done in Iran 1956-1980 the involvement of the right colon was over 40%; but in the present study the involvement of right colon was 27% and sigmoid and left colon 29% , and the rectum 44%. So it can be concluded that the site of colorectal carcinoma has changed in Iran, in the opposite direction with what has happened in the west.